Sagot :
Step-by-step solving: Quadratic Formula
x² + 3x - 27 = 0
a = 1 b = 3 c = -27
Please see the attached file below.
Step-by-step solving: Product of the Roots
For the formula of the product of the roots, please also see the attached file below.
[tex](\frac{-3+3\sqrt{13}}{2})(\frac{-3-3\sqrt{13}}{2}) = \frac{-27}{1}[/tex]
Therefore (∴), the product of the roots of the above equation is -27.
![View image LuisOpelanio2006](https://ph-static.z-dn.net/files/d50/0ed5c8b7e9c2c035e6735fa5c6be14e4.jpg)
![View image LuisOpelanio2006](https://ph-static.z-dn.net/files/dce/a99c578bb2432e6c35abb80ab502e79a.jpg)